What factors are associated with utilisation of health services for the poor elderly? Evidence from a nationally representative longitudinal survey in China - Yanbing Zeng; Weiqian Xu; Xiaomeng Tao (BMJ Open)
Objectives To investigate the status and factors of healthcare service utilisation among the poor elderly in China.Methods We selected the poor elderly from the China Health and Retirement Longitudinal Study (CHARLS) from 2011 to 2015. The main outcome measures include utilisation indicators for the probability and costs of outpatient/inpatient services. Based on modified Andersen behaviour model, a two-part model is designed to analyse the factors of the health service utilisation of the poor elderly.Results The visit rate of outpatient services increased from 15.05% in 2011 to 21.26% in 2015, and the hospitalisation rate increased from 7.26% to 14.32%. The median cost of outpatient and inpatient services in 2015 for the poor elderly were 350 RMB and 10 000 RMB, respectively, and the out-of-pocket ratios were 85.2% and 53.3%, respectively. 78.44% of the people who actually needed healthcare did not use health services, and the main reason was financial difficulties (42.32%). The poor elderly who are higher educated, have children, live in central regions and have social security and a poor health status and who do not smoke or drink are more likely to use health services. The need factor plays a crucial role in determining health service utilisation.Conclusions The poor elderly tends to have a worse health status and a heavier medical burden but had a lower utilisation of health services. Predisposing, enabling, need and health behaviour variables should be considered to improve the health service utilisation and the health of the poor elderly.